Acute Exposure to Altitude. Issue 1 (1st March 2011) - Hodkinson, Peter
Abstract : Acute exposure to altitude principally encompasses aviation and space activities. These environments can be associated with very acute changes in pressure, oxygenation and temperature due to rates and magnitude of ascent that are not experienced in more chronic exposure such as mountaineering. The four key physiological challenges during acute exposure to altitude are: hypoxia (and hyperventilation), gas volume changes, decompression sickness and cold. The brief nature of aviation exposure to altitude provides little opportunity for acclimatisation, leading to markedly different effects when an individual is exposed to the same altitude acutely compared with an acclimatised individual climbing an 8000m (26 347ft) peak. Challenges such as hypobaric decompression sickness are not considered a hazard for chronic altitude exposure but are routine considerations for those flying to high altitude. Protective systems are essential for aircrew and passengers to survive and function during acute exposure to altitude.